Fibroblasts as key cellular targets in acupuncture therapy: a mechanistic perspective - Tu, Shi-Wei; Kawanokuchi, Jun; Takagi, Ken; Liu, Yang-Yang; Li, Yan-Wei; Li, Jun-Yi; Tu, Jia-Yi; Ma, Ning; Guo, Yi (Frontiers in Bioengineering and Biotechnology, 2025)
Acupuncture, a central modality in traditional Chinese medicine, is widely recognized for its clinical efficacy. In recent years, mechanistic studies have shifted from a neurocentric to a broader perspective encompassing the local microenvironment and systemic integration. This review focuses on the pivotal role of fibroblasts in mediating the mechanotransduction processes triggered by acupuncture. We comprehensively summarize current research findings on the contributions of fibroblasts to the therapeutic outcomes of acupuncture and elucidate the multidimensional mechanisms underlying them, especially through mechanical sensing, cytoskeletal remodeling, and the secretion of bioactive molecules. Acupuncture-induced mechanical forces are transmitted via the collagen fiber network to local fibroblasts within the acupoint region, activating mechanosensors and initiating cytoskeletal reorganization and extracellular matrix remodeling. Fibroblasts, in turn, secrete adenosine, hyaluronic acid, inflammatory modulators, and matrix components to mediate analgesic and anti-inflammatory effects directly. Moreover, fibroblasts engage in crosstalk with mast cells and macrophages through chemokine signaling and collagen-mediated mechanical interactions, forming a cellular interaction network that underpins a structural immunity response initiated by acupuncture. This study proposes a mechanobiochemical coupling framework that highlights fibroblasts as key mechanical transducers and regulatory hubs for the therapeutic mechanisms of acupuncture.